Performance enhancement in a solar air heater duct with inclined ribs mounted on the absorber - Skullong, S. (Journal of Research and Applications in Mechanical Engineering, 2018)
The article deals with an experimental study on fluid friction and thermal characteristics in a solar air heater duct roughened artificially with inclined ribs. A new absorber plate with inclined-rib vortex generators is proposed in order to improve thermal performance for energy saving. The experimental work was carried out in the duct having a constant heat-flux on the absorber by varying airflow in the duct to let Reynolds number (Re) be 5300–23,000. Effects of two rib inclination angles (α = 45° and 60°) and three relative rib heights (b/H=BR = 0.1, 0.2 and 0.3) on flow friction and heat transfer behaviors are investigated. The experimental results reveal that the use of inclined rib vortex generators provides the considerable increase in heat transfer over the smoothsurface duct around 3.7–4.7 times while the friction factor (f) increases around 24.4–70.7 times. It is observed that the Nusselt number (Nu) increases with increasing the inclination angle and the relative height. The maximum thermal performance for using the rib vortex generators is about 1.4 at α = 45° and BR = 0.2.